2016
DOI: 10.1002/cne.24137
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transgenic expression of collybistin in neurons of the rat cerebral cortex

Abstract: Collybistin (CB) is a guanine nucleotide exchange factor selectively localized to γ-aminobutyric acid (GABA)ergic and glycinergic postsynapses. Active CB interacts with gephyrin, inducing the submembranous clustering and the postsynaptic accumulation of gephyrin, which is a scaffold protein that recruits GABA receptors (GABA Rs) at the postsynapse. CB is expressed with or without a src homology 3 (SH3) domain. We have previously reported the effects on GABAergic synapses of the acute overexpression of CB or CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Previous studies in this neuronal expression system have shown that wild-type recombinant collybistin isoforms (e.g., CB2 SH3+ , CB2 SH3- , CB3 SH3+ , and CB3 SH3- ) target to and concentrate at GABAergic postsynapses (Chiou et al, 2011). Notably, isoforms lacking the SH3 domain (e.g., CB2 SH3- and CB3 SH3- ) induce the formation of synaptic gephyrin superclusters (Chiou et al, 2011; Fekete et al, 2017) that are accompanied by a significant increase in the amplitude of miniature inhibitory postsynaptic currents (mIPSCs). In this study, we utilized triple-label immunofluorescence with mouse anti-myc, rabbit anti-gephyrin and sheep anti-GAD to reveal exogenous wild-type and mutant collybistin, native gephyrin and GAD, respectively (Figures 3A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in this neuronal expression system have shown that wild-type recombinant collybistin isoforms (e.g., CB2 SH3+ , CB2 SH3- , CB3 SH3+ , and CB3 SH3- ) target to and concentrate at GABAergic postsynapses (Chiou et al, 2011). Notably, isoforms lacking the SH3 domain (e.g., CB2 SH3- and CB3 SH3- ) induce the formation of synaptic gephyrin superclusters (Chiou et al, 2011; Fekete et al, 2017) that are accompanied by a significant increase in the amplitude of miniature inhibitory postsynaptic currents (mIPSCs). In this study, we utilized triple-label immunofluorescence with mouse anti-myc, rabbit anti-gephyrin and sheep anti-GAD to reveal exogenous wild-type and mutant collybistin, native gephyrin and GAD, respectively (Figures 3A–C).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we used CB3 SH3- rather than CB3 SH3+ in our PI3P pull-down and cellular clustering assays. In cultured hippocampal neurones, all tested collybistin isoforms (CB2 SH3+ , CB2 SH3- , CB3 SH3+ and CB3 SH3- ) target to and concentrate at GABAergic postsynapses (Chiou et al, 2011; Fekete et al, 2017) with the major difference being that transfection of de-regulated isoforms that lack the SH3 domain (e.g., CB3 SH3- ) results in large postsynaptic gephyrin and GABA A receptor superclusters, while isoforms containing the SH3 domain induce the formation of supernumerary non-synaptic clusters (Chiou et al, 2011; Fekete et al, 2017). In this system, overexpression of the myc-CB3 SH3- R356Q mutant resulted in a decrease in the overall number of synaptic gephyrin clusters compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NO causes a neurotransmission inhibition through gamma-aminobutyric acid- (GABA-) ergic synaptic communication. It is associated with ion exchange and regulation of membrane excitation [ 21 , 22 ]. Moreover, NO as an important vasodilation factor mediates neurovascular coupling.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure has been described elsewhere (Fekete et al, ; Fekete et al, ; Li, Serwanski, Miralles, Nagata, & De Blas, ; Li et al, ). Briefly, free‐floating brain sections, prepared as described above from P35 SD rats, were incubated with 5% normal goat serum (NGS)/0.3% Triton X‐100/ 0.12 M PB for 1 hour at RT, followed by incubation for 2 days at 4°C in a mixture of primary antibodies raised in different species in 2%NGS/0.3% Triton X‐100 in 0.12 M PB at 4°C.…”
Section: Methodsmentioning
confidence: 99%